Biomethane enhancement from corn straw using anaerobic digestion by-products as pretreatment agents: A highly effective and green strategy. (January 2022) - Ma, Shuaishuai; Wang, Hongliang; Wang, Binshou; Gu, Xiaohui; Zhu, Wanbin
Graphical abstract: Highlights: Anaerobic digestion by-products were used to pretreated corn straw. Methane production was improved by 50.97% after CO2 -liquid digestate pretreatment. The dense structure of straw could be effectively destroyed after pretreatment. Pretreatment at 170 ℃ hindered methane production due to formation of inhibitors. Mechanism behind CO2 -liquid digestate pretreatment was elucidated. Abstract: The development of biogas projects feed by lignocellulosic biomass has been constrained by the high cost of pre- and post-treatment. In this study, a novel strategy for pretreatment by using two by-products, i.e., CO2 and liquid digestate (LD), generated from anaerobic digestion (AD) was developed to overcome these shortcomings. Results showed that corn straw pretreated in LD pressurized under 1 Mpa CO2 at 55 ℃ resulted in increased glucose and xylose contents and a 9.80% decrease in cellulose crystallinity. After 45 days of AD conversion, the methane yield increased by 50.97% compared with untreated straw. However, pretreatment in LD pressurized under 1 Mpa CO2 at 170 ℃ produced 5-hydroxymethylfurfural and furfural, which led to a decrease in methane production from the straw in the subsequent AD conversion. The alteration of the microbial community in the pretreated slurry at 55 °C was another potential contributor to the enhanced performance of AD.